Peri-urban agrifood systems and a landscape project in the southern Mediterranean. The case of the urban agglomeration of Sousse (Tunisia) - Hamrita, Abdelkarim; Jiménez, Daniel Ferrer; Rejeb, Hichem (Frontiers in Sustainable Cities, 2022)
Peri-urban agrifood systems are often subject to urban pressure and other territorial factors, which justifies a detailed study and analysis from multiple points of view. The main objective of this work is to analyze the periurban agri-food systems of the urban agglomeration of Sousse (Tunisia), one of the most important in the country, from a landscape perspective. This work adds to the literature on policies and strategies for the planning and development of Tunisian cities, which are currently facing several environmental and social challenges, of which climate change, food security and sustainable development are the most important. This research focuses, as mentioned above, on the case of the urban agglomeration of Sousse (Tunisia), where the concurrence of different factors (political, environmental, economic, etc.), together with clearly deficient regulations and uncontrolled urban development, is threatening the survival of a traditional, largely family-based agricultural model, based on a mixed or polyculture production system, with olive groves predominating. The latter is vital to ensure the economic maintenance of many families and to actively contribute to food security, with the consequent production of varied, fresh, and quality food. In this sense, we present a specific method that, based on the integrative and strategic significance of landscapes, and on the Landscape Character Assessment methodology, employs the so-called “landscape project” as a tool to strengthen the resilience and sustainability of peri-urban agriculture and to prevent the loss of a landscape heritage that has always been considered crucial for the identity of the local population. The document highlights the importance of the concept of green infrastructure, which, when properly integrated into land-use planning instruments, can contribute to enhancing local and sustainable agri-food systems. It also points out the need to promote Agricultural Parks, a protected status already recognized in Spain and other countries, as instruments for management, promotion, and development, and puts forward some specific proposals for the enhancement and activation of peri-urban agricultural landscapes in the Sousse conurbation. In relation to this last aspect, it insists on the need to modify the current forms of governance, which would require greater leadership and involvement of the main actors in peri-urban agriculture.